Mode of Action of Insecticides. I. Observations on the effect of endrin on blood cell count of some insects. - Trehan, K. N.; Pajni, H. R. (Contributions to Entomology = Beiträge zur Entomologie, 1961)
Preliminary trials were made to determine the effect of endrin on the number of blood cells in cockroaches (Periplaneta american L.), red hairy caterpillars of Amsacta moorei Butler, silkworms (Japanese breed Taihei x Ghoan) and the caterpillars on 'Nargis' (Narcissus poeticus L.). Number of blood cells decreased in the paralysed individuals of cockroaches, red hairy caterpillars and silkworms whereas it increased in the caterpillars of 'Nargis' (Narcissus poeticus). Both the normal and treated insects were exposed to the vapours of acetic acid for 5 minutes to avoid immediate coagulation of blood. Results of the previous workers have been discussed and it has been concluded by the authors that the toxic substances probably bring about a change in the amount of haemolymph which results in the rise or fall of the blood cells per cubic millimeter.